HEADLESS Regulates Auxin Response and Compound Leaf Morphogenesis in Medicago truncatula - Wang, Hongfeng; Xu, Yiteng; Hong, Limei; Zhang, Xue; Wang, Xiao; Zhang, Jing; Ding, Zhaojun; Meng, Zhe; Wang, Zeng-Yu; Long, Ruicai; Yang, Qingchuan; Kong, Fanjiang; et al. (Frontiers in Plant Science, 2019)
WUSCHEL (WUS) is thought to be required for the establishment of the shoot stem cell niche in Arabidopsis thaliana. HEADLESS (HDL), a gene which encodes a WUS-related homeobox (WOX) family transcription factor, is thought to be the Medicago truncatula ortholog of the WUS gene. HDL plays the conserved roles in SAM and axillary meristem (AM) maintenance. HDL is also involved in compound leaf morphogenesis in M. truncatula, however, its regulatory mechanism has not to date been explored. Here, the significance of HDL to leaf development was investigated. Unlike WUS in A. thaliana, HDL was transcribed not only in the SAM and the AM, but also in the leaf. Both the patterning of the compound leaves and the shape of the leaf margin in hdl mutant were abnormal. The transcriptional profile of the gene SLM1, which encodes an auxin efflux carrier, was impaired and the plants’ auxin response was compromised. Further investigations reveal that HDL positively regulates auxin response, likely through the recruitment of MtTPL/MtTPRs into the HDL repressor complex. Its participation in auxin-dependent compound leaf morphogenesis is of interest in the context of the functional conservation and the neo-functionalization of the products of WUS orthologs.